New Graduate Nurses Experience During the Internship Year: Transitioning from a Student to a Professional Nurse - Omer, Tagwa Yousif (South Eastern European Journal of Public Health, 2024)
The global shortage of nursing professionals and increasing healthcare demands, mandates the importance of providing newly qualified nurses with the necessary clinical skills, confidence, and adequate support during their transition from student to professional nurse. Transition of newly graduate nurse to professional practice is challenging and considered as a period of stress, role adjustment and shock reality. The aim of this study is to explore the internship year as a transition period for graduate nurse to professional nurse. Methodology: A longitudinal prospective Cross-Sectional quantitative study included 88 newly graduate nurses throughout the internship year were included using a survey. Result: New graduate nurses indicated that they do not feel comfortable performing independently some of the complex skills or procedure. The sequence of the means of the five sub-scale of the Comfort and Confidence scale were the same in Phase I and II. Support was the highest score followed by professional satisfaction, organizing and prioritizing, then communication and leadership, and last was stress. Results also revealed a highly significant difference between the two phases of internship year. Source of stress was mainly due to transportation, family issues, and job performance. There were significant differences identified in those three factors. It was found that there was different between phase I and II regarding factors that lead to job satisfaction (P < 0.01). Conclusions: This study highlights the need for healthcare and educational organizations to offer necessary support and resources to new graduate nurses during their transition into professional practice.. By addressing areas where new graduate nurses feel less confident and providing opportunities for ongoing learning and feedback, organizations can help new nurses build the knowledge, skills, and confidence they need to provide safe, high quality, and effective patient care.